Digital Banking: Technological Innovation in Financial Inclusion in Peru - Vargas Garcia, Allan Herminio (2022)
Technology-driven digital transformation is impacting the financial sector with the entry of new business models such as fintech and bigtech that successfully compete by offering financial products with disruptive potential. Digital banking is the result of the sum of traditional banking and the internet that offers banking services through a website or mobile application. The integration of financial services into digital ecosystems represents a challenge for traditional banking that needs to evolve to face the changing environment. Digital banking plays an important role in financial inclusion, as it allows access to innovative services to more Peruvians and boosts economic growth. However, a high level of digital fraud also exists, aimed at misappropriating money or blackmailing financial users by means of phishing and the use of malware. Pearson’s correlation coefficient, useful for linear relationships, was used to evaluate the variables “digital banking” and “financial inclusion”, and SPSS-IBM software was used to tabulate the results.